MANAJEMEN KINERJA GURU DI MIN 2 PADANGSIDIMPUAN - Syafaruddin, Syafaruddin; Nuddin, Muhammad; Salim, Salim (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Performance, the true results of the planning and process. Likewise, performance management is important to be carried out at educational institutions, especially the basic education units at the MI/SD level. This paper aims to examine empirically the management of teacher performance in MIN 2 Padangsidimpuan. The focus of the study includes planning, implementing programs, and evaluating teacher performance in MIN 2 Padangsidimpuan. This research uses a naturalistic approach. The collection technique is done by interview, observation, and document review. Next, the data are analyzed through data reduction, data exposure, and drawing conclusions. Data validity is guaranteed by source triangulation techniques and methods. The results of this study indicate that (1) teacher performance planning by conducting teacher performance planning meetings conducted before the new school year begins so that it does not interfere with learning activities. In this activity the division of tasks is carried out according to the teaching decree and the teachers prepare learning tools, especially the lesson plan (RPP), including the media, learning material resources, and evaluation instruments. (2) the implementation of the teacher’s performance program has been running according to the division of tasks and procedures for implementing learning as stipulated in the Decree and roster, as well as conducting a faceprint in accordance with administrative provisions in the madrasa as determined by the Ministry of Religion. (3) evaluation of teacher performance is done through an assessment of lesson plans and learning tools, a list of teaching attendance from the teacher’s faceprint, reporting of learning activities, and reports of student learning outcomes that are in the report card and teacher’s notes.